(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article provides a comprehensive overview of the histological characteristics of exocrine glands, emphasizing their structural diversity and functional significance. Exocrine glands, responsible for secreting substances such as enzymes, sweat, and mucus onto epithelial surfaces, exhibit a wide range of histological features that reflect their varied roles in different tissues and organs. The article discusses the classification of exocrine glands based on their mode of secretion—merocrine, apocrine, and holocrine—as well as their structural organization into unicellular and multicellular forms.